Electroanatomic visualization of coronary arteries: a case series to elicit safety, feasibility and diagnostic value in complex ablation procedures. (19th May 2022) - Fries, B; Johnson, V; Schneider, N; Fraebel, C; Doerr, O; Mathew, S; Hamm, CW; Schmitt, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Although three dimensional (3D) electroanatomic mapping systems allow detailed assessment of anatomy and substrates, ablation still carries substantial risk when close proximity to coronary arteries is suspected. 3D integration of coronary anatomy in mapping systems is still cumbersome, highlighting the need for an option of ad hoc acquirement of coronary artery anatomy. The goal of this case series was to evaluate the feasibility of a wire-based approach to the live visualization of coronary arteries and to assess its diagnostic information regarding procedure guiding. Methods: For this single center case series, we included procedures in which close proximity of an ablation site to an epicardial vessel had to be suspected. An uninsulated-tip wire was then introduced into the relevant coronaries via diagnostic catheters after exclusion of critical stenosis by coronary angiography. The wire was connected to an impedance based 3D mapping system using a clamp and standard pin connection. Integrating this setup in the mapping system allows for live visualization of the wire tip, as well as the assessment of local electrograms within the respective vessel. Results: We included a total of 9 procedures (4 ventricular tachycardia (VT) ablation procedures and 5 procedures for the ablation of premature ventricular contractions (PVCs)). The left coronary arteries were mapped in 8 cases, the right coronary artery was mapped in one case. In the majority of cases, the arrhythmogenic substrate was found in the left ventricle (5/9) or left ventricular summit area and the distal coronary sinus respectively (3/9). In two cases, epicardial mapping was performed combined with visualization of the right or left coronary arteries, respectively. There were no complications attributed to coronary wiring and mapping in this case series. In two cases, the diagnostic information from mapping of the coronary arteries could be used to rule out an epicardial origin of arrhythmia. In the majority of cases, coronary visualization was used to ascertain a proper distance between the ablation site and the vessel. Discussion: In this case series, we could demonstrate the feasibility and safety of coronary artery visualization and its integration in a 3D mapping system. The data obtained was used for diagnostic, as well as safety aspects. The electrograms from the wire were used to quickly assess relative timing of arrhythmias, thus allowing for an estimation of possible epicardial origin. Conclusion: Applying the same caveats as for any other wiring of coronary arteries, their electroanatomic visualization is achieved in a safe and straightforward manner, with minimal technical requirements. Mapping of the coronary arteries adds critical diagnostic information and their real-time visualization is feasible without exceeding costs or risks